Effect of acidic returned fluid on the electric demulsification of crude oil emulsions. Issue 31 (8th April 2015) - Tao, Jun; Shi, Peng; Fang, Shenwen; Li, Keyi; Duan, Ming; Liu, Pingli
<x xml:space="preserve">Abstract</x> The electric demulsification of emulsions in acidic and basic conditions were studied. Two aggregation models of droplets were obtained.